2018
DOI: 10.1007/s41109-018-0097-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact investing market on Twitter: influential users and communities

Abstract: The 2008 financial crisis unveiled the intrinsic failures of the financial system as we know it. As a consequence, impact investing started to receive increasing attention, as evidenced by the high market growth rates. The goal of impact investment is to generate social and environmental impact alongside a financial return. In this paper we identify the main players in the sector and how they interact and communicate with each other. We use Twitter as a proxy of the impact investing market, and analyze relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Yet, the experiment reveals that showing the video had a positive impact in prompting socially oriented decisions, whereby signalling a wider scope for promoting and raising awareness about impact investing. This is confirmed by our logistic regressions and represents one of the most important findings of our research in line with recent studies on the same topic (Novak et al, 2018). Public administration bodies and civil society organisations have already started to put efforts in raising awareness about impact investment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Yet, the experiment reveals that showing the video had a positive impact in prompting socially oriented decisions, whereby signalling a wider scope for promoting and raising awareness about impact investing. This is confirmed by our logistic regressions and represents one of the most important findings of our research in line with recent studies on the same topic (Novak et al, 2018). Public administration bodies and civil society organisations have already started to put efforts in raising awareness about impact investment.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings show that older people have a higher tendency to choose impact investment options than younger people. This is somewhat surprising given the current momentum of narratives such as "Millennials Will Bring Impact Investing Mainstream" (Emerson and Norcott, 2016), whereby young generations are expected to shift large capitals towards social causes, as well as prioritising socially meaningful careers and thus focus on social entrepreneurship (Novak et al, 2018;Stecker, 2014). Nevertheless, some studies have also shown that senior citizens are more prone to contribute to the common good (Molina et al, 2019), due to their willingness to leave a positive legacy behind.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible source to fill this financial gap is emerging in the investment spectrum between traditional investments and philanthropy, namely “impact investing” (Agrawal & Hockerts, 2019; Novak et al., 2018). The Global Impact Investing Network (GIIN, 2018) define impact investing as “investments made into companies, organizations, and funds with the intention to generate social and environmental impact alongside a financial return” (p. 1).…”
Section: Introductionmentioning
confidence: 99%